ANALISIS KEBUTUHAN BAHAN AJAR SEJARAH LOKAL DI SEKOLAH MENENGAH ATAS KABUPATEN MADIUN - Amalina, Sharfina Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Learning local history is very important in the development of education in Indonesia. Local history is able to understand society about the origin of its history, so that the community is able to better deal with the future. Local history learning needs to be maximized in school education, one of which is by adding local history teaching material itself. This research was conducted with the aim to analyze the use of local history teaching materials in learning to support the literacy of local historical culture. This study uses descriptive qualitative methods that involve teachers and students. Research techniques used by observation, interviews, and reviewing several related documents. Observations were made at two high schools in Madiun Regency, namely SMAN 1 Mejayan and SMAN 1 Geger. The results showed that: (1) historical teaching materials used did not support the literacy of local historical culture, (2) students needed additional local history materials that allowed them to conduct research and improve the history of literacy connected with local history.Keywords: literacy; local history; madiun; teaching materials